2020
DOI: 10.3390/w12123447
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Seasonal Sub-Regions of the Drought in the North China Plain

Abstract: Regional climate variability assessment is of great significance in decision-making such as agriculture and water resources system management. The identification of sub-regions with similar drought variability can provide a basis for agricultural disaster reduction planning and water resource distribution. In this research, a modified daily Standardized Precipitation Evapotranspiration Index (SPEI) was used to monitor the spatial and temporal variation characteristics of agricultural drought in the North China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Owing to the vast territory and complex climate [15,61], the spatial-temporal pattern of droughts in China in the last few decades is far from fully understood [23]. Preceding studies focused on variations at the basin and local scales after the 1950s [18,59,60,[84][85][86], which poses a challenge to understanding the drywet variation in each region of China over long time periods [87]. It should be mentioned that in the published articles, the SPEI was not used as the drought index [21,43,73,[87][88][89].…”
Section: Climate Change Characterized By Global Warming Has Become An...mentioning
confidence: 99%
See 4 more Smart Citations
“…Owing to the vast territory and complex climate [15,61], the spatial-temporal pattern of droughts in China in the last few decades is far from fully understood [23]. Preceding studies focused on variations at the basin and local scales after the 1950s [18,59,60,[84][85][86], which poses a challenge to understanding the drywet variation in each region of China over long time periods [87]. It should be mentioned that in the published articles, the SPEI was not used as the drought index [21,43,73,[87][88][89].…”
Section: Climate Change Characterized By Global Warming Has Become An...mentioning
confidence: 99%
“…In this sense, regional water balance is important for the selection of drought indices [34]. A recent study has discussed the applicability of the SPEI in China and found that it is better in humid and sub-humid areas than in arid areas [85]. This is because the ratio of ET anomaly (caused by temperature variation) in the surface water balance is relatively large in arid and semiarid regions with respect to humid regions [95].…”
Section: Influence Of Drought Index Selection On Dry-wet Variationsmentioning
confidence: 99%
See 3 more Smart Citations